THE WHEAT INTROGRESSIVE FORM EVALUATION BY GRAIN BIOCHEMICAL AND TECHNOLOGICAL PROPERTIES - A. I. Abugaliyeva; T. V. Savin (Вавиловский журнал генетики и селекции)
To create stress-resistant, productive and quality wheat varieties, the genetic diversity of wild and cultured relatives is often used – various species belonging to the genera Triticum and Aegilops. Previously, with Triticum militinae, T. timopheevii, T. kiharae, Aegilops cylindrical and Ae. triaristata samples participation, introgressive winter common wheat forms were created and selected for stability and yield. The purpose of this work was to evaluate the biochemical composition and technological grains properties of these forms. Analysis of gluten content in flour by the ISO method revealed a variability level from 28.5 % for the form Erythrospermum 350 × T. militinae to up to 39.6 % for the Zhetysu × T. militinae genotype. In this case, the 1st groups gluten  quality (class “strong”) was found only for the genotypes Erythrospermum 350 × T. militinae (Bezostaya 1 × T. militinae) × T. militinae. According to the physical properties of flour and dough, the introgressive forms vary in the test dilution from 80 to 170 FU  at the level of “filler” and “weak” bread wheat with   the best value for both liquefaction and valorimetric evaluation for the genotypes Bezostaya 1 × Ae. triaristata and Erythrospermum 350 × T. militinae (80 liquefaction units 49 FU and 80–45 FU, respectively). Bread making evaluation for the introgressive forms was comparable with winter wheat varieties including the Almaly standards (720–760 ml) and Karakhan (800 ml), at the bread quality and the baking evaluation. As for hardness, wild relatives and introgressive forms were characterized mainly as medium and hard (52–93 SKCS units). Thus, the introgressive forms studied were mainly related to the “valuable” and “filler” classes according to the technological bakery type evaluation, to the “weak” class according to the flour strength and bread volume, and to the “strong” class at the glutenin HMW composition forecast and the translocation of 1B/1R.